2020
DOI: 10.1155/2020/8836561
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Upper Cervical Cord Infarction: A Report of Two Cases with Mild Neurological Symptoms Accompanying a Small Ischemic Lesion Detected by Brain MRI

Abstract: Spinal cord infarction (SCI) is rare, difficult to diagnose, and often fails to be detected by diffusion-weighted imaging (DWI) of spinal cord magnetic resonance imaging (MRI). Because the clinical features of SCI can vary widely, diagnosis during the acute phase of SCI is often challenging for clinicians. Although SCI shares similar etiologies with cerebral infarction, the characteristics of SCI without vessel dissection remain largely unknown. We present two older patients with mild neurological symptoms who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…A recent clinical study examining cervical cord infarctions in patients with and without vessel dissection showed that lesions were frequently located in the upper cervical cord among patients with dissection. In contrast, patients without J Neuro Spine, 2023 dissection presented with an older mean age of onset and the lesions tended to be located in the lower cervical regions [8][9][10].…”
Section: Introductionmentioning
confidence: 92%
“…A recent clinical study examining cervical cord infarctions in patients with and without vessel dissection showed that lesions were frequently located in the upper cervical cord among patients with dissection. In contrast, patients without J Neuro Spine, 2023 dissection presented with an older mean age of onset and the lesions tended to be located in the lower cervical regions [8][9][10].…”
Section: Introductionmentioning
confidence: 92%